Activity against all odds – the biographical costs of activism and social engagement - Bilon-Piórko, Anna (Adult Education Discourses, 2022)
The paper discusses biographical costs incurred by socially engaged Poles and Polish activists. The analysis of biographical narratives of people from various generations of Polish activists and socially engaged Poles who have been actively involved in various sectors, organisations, and spheres of social life indicates that such commitments produce costs which are strongly dependent on historical contexts and on the kind of activity pursued by the individuals; in addition, there are multiple costs which are shared irrespective of specific historical and situational contexts. The findings also show that socially engaged people are not always aware of some costs they bear, or that they only develop such an awareness after a significant time-lapse, a fact of key relevance to this study and to research into costs of activity in general. The costs themselves are viewed as a dynamic ensemble of interdependent factors, the study of which must examine both individual variables (biographies) and broader social issues.